2015
DOI: 10.1097/fpc.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Association between TAAR6 polymorphisms and airway responsiveness to inhaled corticosteroids in asthmatic patients

Abstract: The TAAR6 rs7772821 polymorphism may be one of the important genetic factors for predicting the response to treatment with inhaled corticosteroids in asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Consistent with this, TAAR1 has been proposed to play a role in the susceptibility to fibromyalgia (Smith et al, 2012), TAAR6 implicated in treatment outcomes 598 in asthma (Chang et al, 2015), and TAAR2, TAAR5, and TAAR9 among the most highly upregulated genes in the inflamed zones of patients with Crohn disease (Taquet et al, 2012), an effect that allowed discrimination of these patients from those with irritable bowel syndrome. As previously indicated, two recent unbiased metabolomic studies have also identified elevated endogenous TAAR1 ligands in Crohn disease fecal samples (Jacobs et al, 2016;Santoru et al, 2017).…”
Section: Effects In the Peripherymentioning
confidence: 64%
See 2 more Smart Citations
“…Consistent with this, TAAR1 has been proposed to play a role in the susceptibility to fibromyalgia (Smith et al, 2012), TAAR6 implicated in treatment outcomes 598 in asthma (Chang et al, 2015), and TAAR2, TAAR5, and TAAR9 among the most highly upregulated genes in the inflamed zones of patients with Crohn disease (Taquet et al, 2012), an effect that allowed discrimination of these patients from those with irritable bowel syndrome. As previously indicated, two recent unbiased metabolomic studies have also identified elevated endogenous TAAR1 ligands in Crohn disease fecal samples (Jacobs et al, 2016;Santoru et al, 2017).…”
Section: Effects In the Peripherymentioning
confidence: 64%
“…Despite minimal knowledge on the biology and physiologic role(s) of TAAR6, several studies have identified single nucleotide polymorphisms (Duan et al, 2004;Chang et al, 2015) and other genetic variants (Pae et al, 2010) in patients with schizophrenia (Duan et al, 2004;Pae et al, 2008a) and affective disorders (Abou Jamra et al, 2005;Pae et al, 2008bPae et al, , 2010. Particularly interesting are the investigations of the potential role of TAAR6 single nucleotide polymorphisms in schizophrenia etiology and treatment, even though results of these studies are somewhat conflicting.…”
Section: Trace Amine-associated Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 33 met the inclusion criteria (Fig. ), with 29 being candidate gene studies (Table S3) and four being GWAS .…”
Section: Methodsmentioning
confidence: 99%
“…Only four SNPs within three genes (CRHR1: rs242941, rs1876828; GLCCI1:rs37973 and FCER2: rs28364072) were positively replicated at least once ( Table 2). Response to medication was assessed using different outcomes: lung function measurements such as changes in FEV1 over time [16][17][18][19][20][21][22][23][24][25][26][27][28][29], annual decline ). in FEV1 [30][31][32], bronchial hyperresponsiveness [BHR] to methacholine [26,29,33,34], asthma symptoms based on questionnaires [25,[35][36][37][38][39][40] and exacerbations despite treatment [37,38,[41][42][43].…”
Section: Candidate Gene Studies Of Icsmentioning
confidence: 99%